2002
DOI: 10.1046/j.1464-410x.2002.02733.x
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between pretreatment serum hormone levels and treatment outcome for patients with prostatic cancer and bony metastasis

Abstract: Objective To evaluate whether pretreatment serum hormone levels are a prognostic factor for prostatic cancer with bony metastasis under hormonal treatment. Between 1980 and1994, 96 patients with prostate cancer and bony metastasis were included for an evaluation by a retrospective review of their charts. All 96 had received hormonal treatment after a diagnosis of metastatic prostatic carcinoma. Serum testosterone, luteinizing hormone (LH), follicle-stimulating hormone (FSH) and prolactin were assessed before t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 27 publications
1
46
0
2
Order By: Relevance
“…(11) 1941 yılında yapmış olduğu çalışmadan beri androjenler ile prostat ve prostat kanseri arasındaki ilişki araştırılmaktadır (12). Özellikle son yıllarda yapılan çalışmalarda metastatik, ileri evre ve kötü prognozlu prostat kanseri saptanan hastalarda serum TTE düzeyinin düşük olduğu gözlenmiştir (9,13,14). Bundan yola çıkarak yapılan çalışmalarda düşük TTE düzeyine sahip hastalarda da (özellikle <3 ng/ml) prostat kanserinin klinik olarak kötü seyirli, patolojik olarak ileri evre ve 5 yıllık nüks oranlarının ise yüksek olduğu gösterilmiştir (15,16,17,18,19).…”
Section: Discussionunclassified
“…(11) 1941 yılında yapmış olduğu çalışmadan beri androjenler ile prostat ve prostat kanseri arasındaki ilişki araştırılmaktadır (12). Özellikle son yıllarda yapılan çalışmalarda metastatik, ileri evre ve kötü prognozlu prostat kanseri saptanan hastalarda serum TTE düzeyinin düşük olduğu gözlenmiştir (9,13,14). Bundan yola çıkarak yapılan çalışmalarda düşük TTE düzeyine sahip hastalarda da (özellikle <3 ng/ml) prostat kanserinin klinik olarak kötü seyirli, patolojik olarak ileri evre ve 5 yıllık nüks oranlarının ise yüksek olduğu gösterilmiştir (15,16,17,18,19).…”
Section: Discussionunclassified
“…47 Paradoxically low pretreatment testosterone predicts a higher likelihood of non-organ confined disease in radical prostatectomy patients, as well as outcome for patients with bone metastatic disease. 48,49 Interestingly, high levels of AR is associated with aggressive clinicopathologic features and with decreased biochemical recurrence-free survival in CaP patients treated with radical prostatectomy. 50 These observations are consistent with reports demonstrating that increases in AR mRNA and protein levels are both necessary and sufficient to convert CaP growth from hormone-sensitive to a hormonerefractory stage, and is dependent on a functional AR ligand-binding domain.…”
Section: Ar and Capmentioning
confidence: 99%
“…40 In fact, there are strong indications that normal testosterone levels play a protective role in the natural history of prostate cancer. Many studies have demonstrated that a low testosterone level prior to treatment is an independent predictor of a more aggressive, highgrade cancer, 20 an increased likelihood of extraprostatic disease at the time of diagnosis, 41 and a decreased likelihood of a favorable treatment response. 42 Nevertheless, most of these trials are limited in sample size and duration of therapy.…”
Section: Resultsmentioning
confidence: 99%